The Effect of Commitment, Empowerment, Controlling on Discipline and Effectiveness of Public Work Employees In Indragiri Hulu - Laura, Netty (Journal the Winners: Economics, Business, Management, and Information System Journal, 2015)
The research was conducted in Department of Public Works employee Indragiri Hulu. The purpose of this research was to know the influence of commitment, empowernment, and controlling towards the discipline with individual test and overall test, and to know the influence of discipline toward the effectiveness of the Department of Public Works employee Indragiri Hulu. The research method applied descriptive quantitative and the population in this research were 118 employees. By using a Purposive Random Sampling method, it has been obtained 92 respondents. Data obtained with questionnaires. This research used Two phase Multiple Regression Analysis. The result of research shows that the commitment, empowernment, and contolling have been influence of significant toward the discipline. It indicates from the value of Fobs> Ftable at the level of α = 5%           Fobs=38,261>Ftable = 2,48 with probability (p) smaller than 0,05 and determination coefficient value (R2) is 56,6%. It means that 56,6% commitment, empowernment, and controlling toward the employee’s discipline. A partially (individual test) shows that the value of commitment 2,369, empowernment -0,04, controlling 7,811. This result indicates that commitment and controlling have most dominant influence on employee’s discipline, empowerment has no influence on the discipline of employee. Discipline has been influence of significant toward the effectiveness (p<0,05) with tobs =3,503> ttable = 1,66298